Contraception in Adolescence: Literature Review - Ana Beatriz Santos Reis; Ianê Nogueira do Vale (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Abstract: It is worrisome to the public health the fact that adolescents are the portion of the population which has increased the fertility rate in recent years. This article aims to identify the reasons in the literature why adolescents are still presenting risk behavior despite of being informed about contraceptive methods. Two computerized databases were consulted: LILACS (Latino-American and Caribbean Health Sciences Literature) and MEDLINE (International Database for Medical Literature). It has been found 128 articles, from which 16 were chosen to fit more to the proposed research. After analyzing the article, the discussion was based on the main issues addressed by the studies: the level of knowledge of adolescents about contraceptives, the age of first sexual intercourse, the most used contraceptive method, the factors related to the no using of contraceptives, the use of methods related to the sex of the adolescent and the use of drugs related to the contraception. The research enabled to note the complexity of the factors that determine the behavior of young people about contraception. The data indicated can help to develop ways of dealing with adolescents and create different strategies to achieve healthy behaviors. There is also a need to develop educational strategies that address the matter in multiplies dimensions.